Deficits in Emotional Clarity and Vulnerability to Peer Victimization and Internalizing Symptoms among Early Adolescents - Hamilton, Jessica L. (J Youth Adolesc, 2015)
Peer victimization is a significant risk factor for a range of negative outcomes during adolescence, including depression and anxiety. Recent research has evaluated individual characteristics that heighten the risk of experiencing peer victimization. However, the role of emotional clarity, or the ability to understand one’s emotions, in being the target of peer victimization remains unclear. Thus, the present study evaluated whether deficits in emotional clarity increased the risk of experiencing peer victimization, particularly among adolescent girls, which, in turn, contributed to prospective levels of depressive and anxiety symptoms. In the present study, 355 early adolescents (ages 12–13; 53% female; 51% African American) who were part of the Adolescent Cognition and Emotion project completed measures of emotional clarity, depressive symptoms, and anxiety symptoms at baseline, and measures of peer victimization, depressive symptoms, and anxiety symptoms at follow-up. Moderation analyses indicated that deficits in emotional clarity predicted greater peer victimization among adolescent girls, but not adolescent boys. Moderated mediation analyses revealed that deficits in emotional clarity contributed to relational peer victimization, which, in turn, predicted prospective levels of depressive and anxiety symptoms among adolescent girls, but not boys. These findings indicate that deficits in emotional clarity represent a significant risk factor for adolescent girls to experience relational peer victimization, which, in turn, contributed to prospective levels of internalizing symptoms. Thus, prevention programs should target deficits in emotional clarity to prevent peer victimization and subsequent internalizing symptoms among adolescent girls.